THE INFLUENCE OF MOTHER TONGUE ON THE SPEAKING ABILITY OF SANGIHE ENGLISH STUDENT IN UNIVERSITAS NEGERI MANADO - Mutiara Baule; Nihta V. F. Liando; Sarah Kamagi (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
This study aims to show how the difficulties faced by English students from Sangihe in learning English, especially in terms of speaking ability. This research was done by using qualitative method. The data comes from Sangihe students that is currently studying in English Education Department in Universitas Negeri Manado. In collecting the data the researcher used interview technique which involves 7 students that are originated from Sangihe. The data was analyzed by using Miles & Huberman’s method; data reduction, data presentation and conclusion. The result of the study shows that mother tongue does affect students’ learning ability especially in learning speaking of English language. It shows that mother tongue impacts students psychologically as they feel afraid and not confident in speaking English. Furthermore, it affects the student speaking ability as they find it harder to learn English grammar and vocabulary while having Sangihe as their mother tongue, and, their environment also affects them as they found people are commenting if they falsely utter an English word. It can be concluded that mother tongue does affect someone’s ability in speaking English psychologically, grammatically and environmentally. Psychologically, it makes the student shy and not confident. Grammatically, it affects their pronunciation and environmentally, it affects their behavior of being criticized